Clinico-bacteriological profile of non-traumatic perforation peritonitis cases attending a tertiary care hospital of central India region - Meshram, Sunita; Lal, Manoj (International Surgery Journal, 2018)
Background: Peptic ulcer, typhoid and appendicitis constitute the common causes of non-traumatic perforation, tuberculosis, ascariasis, amoebiasis and roundworm infestation are less common. An increasing incidence of perforation of gastrointestinal tract provoked us to study various aspects of non-traumatic perforation of gastrointestinal tract. Methods: The present study was carried out in 165 patients of non-traumatic gastrointestinal perforation, admitted in the surgical wards of sanjay Gandhi Memorial Hospital associated with S. S. Medical College, Rewa (M.P.), India, in the period from August 2002 to July 2003. All medical and surgical management was done, and necessary investigations were performed. A careful record of pre, per and postoperative findings were made in each in the proforma. All the cases were advised to attend surgical outpatient Department regularly for follow up. Results: Maximum number of cases were due to peptic perforation 70.91% followed by typhoid perforations 26.06% and appendicular perforations 3.03%. Highest incidence of peptic perforation was recorded in the age group of 41-60 years (42.74%), typhoid perforation in age group of 21-40 years (42.74%), typhoid perforation in age group of 21-40 and 41-60 years of age group (40%). Pain abdomen was present in all cases of perforations Next common symptoms in peptic perforations was constipation and distension (90.5%). In typhoid perforations distension constipation (93.03%) followed by abdominal distension (83.72%) and in appendicular distension (80.0%) followed by abdominal distension (40.0%) cases. 51.2%cases of peptic perforation were operated, 58.1% typhoid perforations were operated and 100% cases of appendicular perforation were operated. Conclusions: It is concluded from the study that non-traumatic gastrointestinal perforation is a common emergency surgical problem encountered by a general surgeon. The need for an early and accurate management is necessary, because if not treated timely the result will be fatal.